TRANSFORMATION OF MODERN MANAGEMENT THROUGH ARTIFICIAL INTELLIGENCE - Nawawi, Soiman; Fian, Khafifatul (Jurnal Kajian Pendidikan dan Psikologi, 2025)
The rapid advancement of Artificial Intelligence (AI) has transformed the paradigm of modern management toward a data-driven, intelligent, and adaptive system. This study explores the optimization strategy of AI-based management through the concept of data-driven governance, emphasizing the integration of technology, human resources, and organizational culture. AI no longer serves merely as an operational tool but as a strategic instrument in data processing, analysis, and decision-making. By utilizing AI, organizations can enhance efficiency, accuracy, and innovation while fostering transparency and accountability in managerial processes. The discussion highlights three key dimensions of AI-based management optimization: strengthening human resource capacity, enhancing media literacy, and developing ethical data governance. These dimensions ensure that the application of AI aligns with organizational values and social responsibility. However, challenges remain, including algorithmic bias, data security, and the need for structural and cultural readiness. Therefore, the success of AI implementation depends on the establishment of a mature digital ecosystem supported by ethical governance and continuous human adaptation. In conclusion, AI-based management optimization represents a transformative shift from traditional managerial practices to intelligent governance, balancing technological progress with human values to achieve sustainable, transparent, and competitive organizational systems.